Kisspeptin increases intracellular calcium concentration by protein kinase C-mediated signaling in the primary cultured neurons from rat hippocampus - Serhatlioglu, Ihsan; Yuksel, Hande; Kacar, Emine; Ozcan, Sibel; Canpolat, Sinan; Ozcan, Mete; Kelestimur, Haluk (C M B Assoc, 2018)
In addition to the fact that kisspeptin and its receptor GPR54 are well known to be abundantly expressed in the hypothalamus with suggestive roles in the initiation of puberty and similar reproductive system properties, there is also proof showing that kisspeptin might have influences on hippocampal functions. In our previous study, it was shown that kisspeptin increased free intracellular Ca2+ values ([Ca2+] i) through protein kinase C ( PKC) activation in GT1-7 cells. For this reason, we examined the influences of kisspeptin on [Ca2+] i in hippocampal neurons to determine if kisspeptin shows its effects on hippocampus through the same mechanism. Hippocampal neurons were excised from the brains of fetuses on 17th embryonic day from maternal rats. The influences of kisspeptin on [Ca2+] i in hippocampal neurons were examined through in vitro calcium imaging system. The responses of [Ca2+] i to kisspeptin were quantified by the changes in 340nm/ 380nm ratio. Kisspeptin- 10 caused [Ca2+] i transients in hippocampal neurons. The change in [Ca2+] i by 100 nM kisspeptin was prevented by pre- treating the cells in PKC inhibitor chelerythrine chloride. According to the results, kisspeptin activates intracellular calcium signaling in hippocampal neurons via the pathway that depends on PKC. The results of this study suggest that kisspeptin may have a role in hippocampal neuron functions.
Keywords: Kisspeptin; Calcium; Hippocampus; Protein kinase C; Calcium imaging